Incidence of lactic acid bacteria and Aspergillus flavus in brewer's grains and evaluation of potential antifungal activity of these bacteria - Asurmendi, Paula (2014)
Feed destined for animal production as brewer's grains can be contaminated by Aspergillus section Flavi species. Lactic acid bacteria (LAB) play a defining role in the preservation and microbial safety of fermented foods. The objective of this study was to study the incidence of lactic acid bacteria, Aspergillus section Flavi and AFB1 in brewer's grains and the preliminary antifungal activity of native LAB in vitro. LAB and aflatoxigenic Aspergillus were found in high counts in brewer's grains used as raw material for pig feedstuff. However, AFB1 had low AFB1 natural incidence in samples. In vitro antifungal activity of LAB isolated showed that all bacteria tested inhibited two Aspergillus flavus strains assayed. The high incidence of LAB could be inhibiting the AFB1 production in by-products obtained from the beer industry. LAB strains with excellent antimicrobial activity were also found in this substrate.